Hydration properties of alkali-activated fly ash/slag binders modified by MgO with different reactivity. (December 2021) - Wang, Z.; Park, Solmoi; Khalid, Hammad R.; Lee, H.K.
Abstract: The roles of MgO in alkali-activated materials have attracted much attention in recent decades. The effects of the reactivity of MgO on the compressive strengths and hydration properties of alkali-activated materials consisting of a blend of fly ash, slag, and MgO were studied here. The alkalinity of the activator, vital to the dissolution and hydration mechanisms of MgO, was investigated as well. It was found that MgO reactivity had little influence on the crystallization of C–S–H type gels, while increasing the MgO reactivity prompted incorporation of Na and Mg atoms into amorphous binding chains within the binders. A higher hydration degree of MgO and alkali-activated materials can be achieved by using highly reactive MgO, as revealed by crystallinity and hydration analyses. The hydration mechanism of reactive MgO in the alkali-activated fly ash and slag blended materials is discussed. Highlights: Large strength (>50 MPa) was gained by moderately reactive MgO blended fly ash/slag. Highly reactive MgO prompted the hydration of amorphous binding gels. Improving the reactivity of MgO induced a higher incorporation of Na and Mg within amorphous binding matrix. A moderate alkalinity at 5 M enhanced hydration products and compressive strengths of samples.